Advances in Security Research in the Asiacrypt Region. - RAPHAËL CW PHAN; MASAYUKI ABE; LYNN BATTEN; JUNG HEE CHEON; DAWSON, ED; GALBRAITH, STEVEN; JIAN GUO; LUCAS HUI; KWANGJO KIM; XUEJIA LAI; DONG HOON LEE; MITSURU MATSUI; et al. (Communications of the ACM, 2020)
The article discusses advances and developments in security research in the Asiacrypt region, particularly the work of conferences of the organization the International Association for Cryptologic Research (IACR).